Evaluation Of Renal Safety Of Raas Inhibitor Therapy: A Clinical And Pharmacovigilant Study - Khaleel, Mohammad Ali Mohammad (2024)
After initiating a renin-angiotensin-aldosterone system (raas) inhibitor, there is a risk of decreased renal functions or hyperkalaemia. Hence, biochemical monitoring tests for serum creatinine and potassium are warranted after therapy initiation and are mandatory by guidelines. However, adherence to the guidelines for performing these monitoring tests has been reported to be low globally, with unknown rates in malaysia. Additionally, the prevalence of serum creatinine increase by ≥30% or hyperkalaemia in malaysia after initiating raas inhibitors remains unknown. Using data from hospital universiti sains malaysia (husm) from 2010 to 2020, we studied serum creatinine increase and hyperkalaemia prevalence, along with this monitoring tests adherence. Adherence within 15 and 60 days of raas inhibitor initiation was 6.7% and 20.3%, respectively. Incidence rates of serum creatinine increase within 15 and 60 days were 4.9% and 6.7%, and for hyperkalaemia, 1.6% and 1.9%, respectively. An ensembled machine learning algorithm was developed using husm data to predict a ≥30% increase in serum creatinine within 60 days, showing robust performance metrics (auc: 0.945, accuracy: 0.959, precision: 0.737, sensitivity: 0.583, specificity: 0.985, balanced accuracy: 0.784). The predictive model would help physicians to easily highlight patients at high risk, make sure those patients will not miss the monitoring tests, and give physicians a chance to be proactive with patients’ treatment plans rather than reactive. For a more comprehensive study, we utilized the fda adverse event reporting system (faers), one of the world's largest pharmacovigilance databases, covering data from january 2004 to september 2021.